The German financial sector: Male dominance in top decision-making bodies remains pervasive - Elke Holst; Julia Schimeta (DIW Economic Bulletin, 2013)
In the German financial sector, the majority of employees are women, but it is still men who hold the top positions. With women making up only 4.2 percent of the boards of the largest banks and savings banks, they were still vastly underrepresented at the end of 2012 (up 1 percentage point from the end of 2011). The story is similar on the boards of the major insurance companies. The situation is somewhat better on supervisory boards: At the largest banks and savings banks, women made up 17.8 percent of all board members at the end of 2012 (up 1.2 points), and 15.3 percent at insurance companies (up 2.2 points). The vast majority of these women are employee representatives, but the percentage of women being appointed as shareholder representatives is increasing. If the financial sector does not make significant progress in achieving more representation for women in top decision-making bodies in the foreseeable future, political pressures on them to do so will likely increase. This also applies to top positions in the ECB and the Financial Market Authority.
Keywords: G2; J16; J78; L32; M14; M51; 330; financial sector; board diversity; women CEOs; gender equality; management; public and private sector banks; insurances companies